Аnalysis of efficiency of oil sorption methods of wastewater treatment - Павлюх, Л.І.; Матвєєва, О.Л.; Зубченко, О.М. (Proceedings of National Aviation University, 2006)
The sorbtional methods of purification of waste waters are considered. Conduct analysis of effectiveness some sorbents.